THE ABUNDANCE AND DIVERSITY OF ECHINODER IN TIDAL ZONE OF CINGKUAK ISLAND AND PASUMPAHAN ISLAND WEST SUMATRA - Raya, Rosanti Dina; Tanjung, Afrizal; Ikhwan, Yusni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research carried out in June 2013 on the island of Pasumpahan Cingkuak and West Sumatra Province. The purpose of research is to determine the abundance and diversity of Echinodermata. The method used in this research is a survey method. Echinoderms types found in Cingkuak Island consists of three species classified into two classes, namely Asteroidea and Holothuridea. While the types of echinoderms are found in Pasumpahan consists of seven species are classified into three classes, namely Asteroidea, Ophiuroidea and Holothuridea. The type and amount of echinoderms contained in Pasumpahan more than Cingkuak Island. From calculations mennjukkan abundance in Pasumpahan higher than abundance on the island Cingkuak, respectively 18.65 and 5 ind / m2. For echinoderm species abundance Cingkuak Island which has the highest individual is kind Culcita schimedeliana with a value of 3 ind / m2 and the lowest abundance of individual species is of type Culcita novaeguineae and Synapta maculata which each have a value of 1 ind / m2. While the abundance of individual species is highest in Pasumpahan of sea cucumber Holothuria atra type with a value of 4.5 ind / m2, Holothuria scabra with a value of 4.4 ind / m2, and the lowest individual types of starfish species Culcita novaeguineae with the value of 1.25 ind / m2, and Synapta maculata with value 1 ind / m2. Based on observational data and the results of the data analysis of the value of diversity index at each study site, echinoderms diversity in Pasumpahan higher than Cingkuak Island is 1.3712 to 2.2879 on the island of Cingkuak and Pasumpahan.Keywords: Cingkuak Island, Pasumpahan, Echinodermata, AbundancePENDAHULUAN